Protein storage with perfluorinated PEG compartments in a hydrofluorocarbon solvent. Issue 44 (12th September 2016) - Koda, Yuta; Terashima, Takaya; Maynard, Heather D.; Sawamoto, Mitsuo
Abstract : We report a novel storage technology of proteins with surface-perfluorinated poly(ethylene glycol) compartments in 2 H, 3 H -perfluoropentane. Abstract : We report a novel storage technology of proteins with surface-perfluorinated poly(ethylene glycol) compartments in 2 H, 3 H -perfluoropentane. The compartments were obtained from self-folding and self-assembly of an amphiphilic random copolymer bearing poly(ethylene glycol) and perfluoroalkyl pendants in the hydrofluorocarbon. Lysozyme and α-chymotrypsin as model proteins were efficiently encapsulated within the PEG compartments and quantitatively recovered therefrom with water. The recovered lysozyme maintained the original higher order structure without denaturation to show enzymatic activity for the hydrolysis of Micrococcus lysodeikticus as high as its original counterpart in water. The storage technology was further effective to inhibit inactivation of α-chymotrypsin.